2012
DOI: 10.1111/odi.12030
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes functionalized with sodium hyaluronate restore bone repair in diabetic rat sockets

Abstract: Our results indicate that HY and HY-CNT restore bone repair in the tooth sockets of diabetic rats, suggesting that these biomaterials are potential adjuvant therapies for the management of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 24 publications
0
16
0
3
Order By: Relevance
“…HY-CNTs have been reported to accelerate the bone repair process in rats following an interval of 7 days after extraction of the upper first molar, when applied to the tooth sockets (9). They have also been shown to enhance bone repair in the tooth sockets of diabetic rats, suggesting usefulness in therapies for bone reconstruction in adverse metabolic states (10). CNTs are allotropic forms of carbon in which a hexagonal matrix is arranged along cylindrical surfaces with diameters on the order of nanometers and lengths on the order of micrometers.…”
Section: Introductionmentioning
confidence: 99%
“…HY-CNTs have been reported to accelerate the bone repair process in rats following an interval of 7 days after extraction of the upper first molar, when applied to the tooth sockets (9). They have also been shown to enhance bone repair in the tooth sockets of diabetic rats, suggesting usefulness in therapies for bone reconstruction in adverse metabolic states (10). CNTs are allotropic forms of carbon in which a hexagonal matrix is arranged along cylindrical surfaces with diameters on the order of nanometers and lengths on the order of micrometers.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] In addition, in closely related bioengineering fields, chemically modified CNTs alone or in combination with distinct composite materials have been applied to facilitate neuronal growth, cartilage, and myocardial tissue differentiation, among other applications. [20][21][22][23][24][25][26][27][28][29][30][31][32] Furthermore, CNTs in suspension have also been investigated as potential carriers for drug delivery, and have been shown to have no effect on vital functions of cells. 31,32 In the current work, we have evaluated the bone-inducing properties of carboxyl (COOH)-modified CNTs by conducting in vitro experiments on two models of progenitor cells, human fetal osteoblasts (hFOBs) and murine embryonic stem cells (mESCs), and we have further investigated bone induction in vivo in a rat model.…”
Section: Introductionmentioning
confidence: 99%
“…Corroborating these findings, it has been reported that HY and HY-SWCNTs accelerate the bone repair of tooth sockets of normal and diabetic rats [Mendes et al, 2008;Sá et al, 2013]. Nevertheless, these studies were performed using tooth sockets as a model for bone defect, which is a very small defect in a spongy bone.…”
Section: Discussionmentioning
confidence: 91%
“…In this context, we have previously demonstrated that HY and HY-CNTs were able to accelerate the healing process of tooth sockets of normal and diabetic rats after tooth extraction [Mendes et al, 2008;Sá et al, 2013;Martins-Júnior et al, 2016] without any significant changes in the cardiovascular function of animals [Joviano-Santos et al, 2014]. These studies were performed using tooth sockets as a model for bone repair, which is a very small area in a spongy bone.…”
Section: Introductionmentioning
confidence: 99%